The chemistry of hydrocarbon fuels - Schobert, Harold H., 1943- (Butterworths, 1990)
The Chemistry of Hydrocarbon Fuels is concerned with the chemical aspects of hydrofuels such as coal, petroleum, and natural gas. Topics covered include diagenesis and catagenesis, processing of natural gas and petroleum fractions, coal combustion, and chemicals that can be obtained from fuels. This book is comprised of 14 chapters and begins with a comprehensive treatment of the formation of fuels from accumulated organic matter, along with the organic geochemistry of coal, oil, and gas. The following chapters focus on the composition of hydrocarbon fuels and some of their important physical.